Can mentoring assist in the school-to-work transition? - Lang, Martin [Verfasser] (My University, 2010)
"Due to recent bottlenecks in the apprenticeship market the transition from general schooling into the German employment system has become more and more problematic for many pupils over the past years. In particular, young persons with migrant backgrounds, low academic achievement or missing school graduations need special help from 'Managing transition' projects. The purpose of this paper is to present some findings from a formative evaluation of a mentoring project. The evaluation of the mentoring programme was done in a case study manner. A formative evaluation design with a three-part survey was chosen. As a result of the formative evaluation, some recommendations are given that should optimise the continuation and extension of the mentoring programme." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; P 2.1 Schulabgänger; P 1.7 Benachteiligte; P 1.1 Jugendliche; P 3.1.3 Coaches, Supervisoren, Moderatoren; S 2.3.2 Programme in der Berufsbildung; Berufseinmündung; Zweite Schwelle; Übergangsmanagement; Schulabgänger; Benachteiligter Jugendlicher; Mentoring; Programm; Evaluation; Fallstudie